OVERLAP AND OBESITY IN CHILDREN OF PUBLIC CRECHE (Fiep Bulletin - online, 2017)
Obesity has become a worldwide epidemic and worry in childhood is becoming more worrying,especially for the future that the child may have when it becomes adult and remaining obese. The objective of the present study isto investigate overweight and obesity in public day care children aged 4 to 6 years in a public day care center in Vitória. Thesample consisted of 79 children of both sexes, 35 boys with 5.29 ± 0.83 years and 44 girls with 5.17 ± 0.96 years. The body massindex found in boys was 16.37 ± 1.92 kg / m2 and in girls it was 16.67 ± 1.80 kg / m2. From the study, it was possible to observe,unlike the evident tendency in Brazil, characterized by the increase in the prevalence of overweight and obesity in detriment of thelow weight rates.
Keywords: obesity; children; body mass